Pengetahuan Ibu Menopause tentang Gizi Seimbang pada Masa Menopause di Wilayah Kerja Puskesmas Awang Besar, Barabai, Hulu Sungai Tengah - Riska Pebrianti; Ika Lestiani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Women were considered menopausal if the woman does not menstruate again within 12 months without any particular intervention. Data from the working area of health centers Awang Besar Hulu Sungai Tengah in 2014 there are 463 menopausal womens. The purposes of this study was to know knowledge of menopause woman about balanced nutrition in menopause period at the regional of Puskesmas Awang Besar, Barabai, Hulu Sungai Tengah. This study was used descriptive with cross-sectional design. The population are menopause women who willing to become respondents in Puskesmas Awang Besar, Barabai, Hulu Sungai Tengah. Samples was obtained by simple random sampling technique which consisted of 83 respondents. The results showed that majority of respondents in the range aged 48-55 years and have less knowledge about nutrition balanced during menopause were 47 respondents (57.32%). In conclusion, there was less of knowledge about balanced nutrition in menopause period toward menopause woman in Puskesmas Awang Besar, Barabai, Hulu Sungai Tengah.